1995
DOI: 10.1364/ol.20.002057
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of mid-infrared radiation in an AgGaxIn_1−xSe_2 crystal

Abstract: Efficient generation of mid-infrared radiation by noncritically phase-matched second-harmonic generation is demonstrated in a mixed chalcopyrite crystal, AgGa(x)In(1-x)Se(2), and compared with that in an AgGaSe(2) crystal. Nonlinear coeff icients d(36) of AgGa(x)In(1-x)Se(2) and AgGaSe(2) crystals have also been derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…It is shown that the growth steps are parallel to each other, and the intervals are not equal. This phenomenon indicates that the as-grown crystal is homogeneous [12]. In order to overcome the inhomogeneity caused during crystal growth, the precise temperature control during the crystal growth and heat treatment on the as-grown crystal were used to improve the homogeneity of the crystal.…”
Section: Sem Observationmentioning
confidence: 99%
“…It is shown that the growth steps are parallel to each other, and the intervals are not equal. This phenomenon indicates that the as-grown crystal is homogeneous [12]. In order to overcome the inhomogeneity caused during crystal growth, the precise temperature control during the crystal growth and heat treatment on the as-grown crystal were used to improve the homogeneity of the crystal.…”
Section: Sem Observationmentioning
confidence: 99%
“…The chalcopyrite AgGaSe 2 (AGSe) is a well-known ternary semiconductor used in many applications like the generation of second and third harmonic frequencies of CO 2 laser output [1][2][3], preparation of Schottky diodes [4], x-and gamma-ray detectors [5] and solar cells [6]. Thin film solar cells based on the CuIn 1−x Ga x (S 1−y Se y ) 2 (CIGSSe) chalcopyrite material system have reached efficiencies of about 20% in the laboratory [7] and 13.4% on large areas (3459 cm 2 ) [8] using a simple heterostructure consisting of ZnO/CdS/CIGSSe/Mo/glass.…”
Section: Introductionmentioning
confidence: 99%
“…On the question of mixed chalcopyrite crystals, although due importance is attached to our pioneering work 14,15 in AgGai_ I In J Se 2 crystal for near-noncritical SHG with CO2 laser, other crystals of importance hâve been left out. Hère, in addition to increase in conversion efficiency and realization of noncritical phase matching (NCPM) for SHG over AgGaSe 2 crystal, NCPM for THG for C0 2 laser radiation has since also been reported.…”
Section: Additional Information On Emergence Of Chalcopyrites As Nonlmentioning
confidence: 99%